BAR, computers, and publication: past, and present - Rahtz, S (Tempus Reparatum, 1996)
Introduction In considering the relationship between archaeological computing, and the history of British Archaeological Reports (henceforth BAR) , we may wish to ask three questions: 1. What did BAR do for archaeological computing? 2. What are the current problems in archaeological publication that can be solved with information technology? 3. What would BAR do if it was set up now? The purpose of this brief paper is to try and answer these points, and in particular question whether BAR was important actually for its publications, or for the social phenomenon which it represented. I deliberately here use the past tense — it was the quantity of BAR volumes in its heyday which made it truly distinctive in a way which the (very fine!) new operation by Tempus Reparatum cannot match. I suggest that the current enthusiasm for the World Wide Web may be comparable to the origins and effect of BAR.